THE ROLE AND IMPORTANCE OF ARTIFICIAL INTELLIGENCE IN TEACHING PROGRAMMING FUNDAMENTALS (Educator Insights: Journal of Teaching Theory and Practice, 2026)
The rapid evolution of Artificial Intelligence (AI) has significantly impacted various sectors, with education being one of the most transformed. In the realm of Computer Science, specifically the teaching of programming fundamentals, AI tools are shifting the pedagogical landscape from traditional lecture-based methods to personalized, adaptive learning experiences. This article explores the multifaceted role of AI in assisting both educators and students, focusing on its ability to provide real-time feedback, automate grading, and offer customized learning paths. While highlighting the benefits, the paper also addresses the ethical implications and the necessity of maintaining a balance between AI assistance and the development of core problem-solving skills.